Effect of the locational relationship between the 1st wave dominant follicle and the corpus luteum on conception rate after embryo transfer: data analysis of 297 embryo transfers from a commercial embryo production program - Goto, Akira; Hayama, Koh; Urakawa, Manami; Oono, Yoshio; Hazano, Ken; kayano, Mitsunori; Haneda, Shingo; Nakada, Ken; Matsui, Motozumi (Journal of the Hellenic Veterinary Medical Society, 2022)
The ovarian structures identified at the time of ET are important for the selection of recipients. In previous report, the first-wave dominant follicle, located ipsilateral to the corpus luteum on the ovary, was associated with reduced conception rate after artificial insemination. Thus, a similar locational relationship may affect conception rate during embryo transfer. Data from 297 transfers of fresh embryos to virgin heifers were analyzed aiming to check the effect of first-wave dominant follicle location in relation to the corpus luteum on conception rate using a multivariable logistic regression model with six confounders. The location of the first-wave dominant follicle in relation to the corpus luteum location had no significant effect on conception rate, suggesting that it is not necessary to consider the firstwave dominant follicle size and location in the ovaries for recipient selection.